2010
DOI: 10.1038/nature09644
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a spin-aligned neutron–proton paired phase from the level structure of 92Pd

Abstract: 3The general phenomenon of shell structure in atomic nuclei has been understood since the pioneering work of Goeppert-Mayer, Haxel, Jensen and Suess [1].They realized that the experimental evidence for nuclear magic numbers could be explained by introducing a strong spin-orbit interaction in the nuclear shell model potential.However, our detailed knowledge of nuclear forces and the mechanisms governing the structure of nuclei, in particular far from stability, is still incomplete. In nuclei with equal neutron … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(89 citation statements)
references
References 25 publications
3
83
0
Order By: Relevance
“…The knowledge of the underlying shell structure of nuclei in the vicinity of 100 Sn has to be determined with the highest possible accuracy to answer the burning questions in the nuclear structure, like the possibility of a new coupling scheme which might develop in the N=Z nuclei in the vicinity of 100 Sn [25]. The present measurement consists in a stringent test for LSSM calculations, in which the realistic character of such a coupling scheme still needs to be probed.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of the underlying shell structure of nuclei in the vicinity of 100 Sn has to be determined with the highest possible accuracy to answer the burning questions in the nuclear structure, like the possibility of a new coupling scheme which might develop in the N=Z nuclei in the vicinity of 100 Sn [25]. The present measurement consists in a stringent test for LSSM calculations, in which the realistic character of such a coupling scheme still needs to be probed.…”
Section: Discussionmentioning
confidence: 99%
“…The low-lying yrast states in 92 46 Pd were recently reported [62]. This is the heaviest N = Z nucleus with measured spectrum so far.…”
Section: Seniority and Np Coupling Schemesmentioning
confidence: 99%
“…It was suggested that in this nucleus, as well as in neighboring nuclei like 96 Cd, the properties of the low-lying states can be classified by a spin-aligned np pair coupling scheme [62,63]. That is, the ground state wave functions do not consist mainly of pairs of neutrons (νν) and protons (ππ) coupled to zero angular momenta, but rather of isoscalar np pairs (νπ) coupled to the maximum angular momentum J, which in the shell 0g 9/2 is J = 9 [62,63]. A detailed shell-model analysis of the spinaligned np pair coupling was performed in Refs.…”
Section: Seniority and Np Coupling Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarities between the doubly magic nuclei 146 Gd and 208 Pb [1] and the expected influence of the proton-neutron interaction on structural features as observed in the 100 Sn region [3,[8][9][10]] also fueled further interest. As a result, a wealth of nuclear structure data has become available.…”
Section: Introductionmentioning
confidence: 99%